Analyzing Utilization Of Mental Health Services for National Health Insurance Participants in Indonesia - Rahmah, Rizqi Habiibah; Indrawati, Fitri (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Utilization of mental health services In Indonesia is still low, while the need for mental care is relatively high. Poor mental conditions will affect individuals in deploying their abilities or potential, leading to any daily pressure that is difficult to cope with. Prior to National Health Insurance (JKN), financing for mental health services was based on fee for service (out of pocket). Currently, the government is trying to grant access to mental health services with the JKN system in primary, secondary, and tertiary services. Implementing the JKN policy is expected to escalate the community's access to mental health. Since JKN was implemented in 2014, no one has seen how JKN participants actively participate in mental health services. This study will reveal how the participants utilized JKN mental health services in 2020. This quantitative study used a nested case-control design to take secondary data on BPJS Health Sample Data for 2015-2020. The bivariate analysis results using the chi-square test point out a significant relationship between age, marital status, FLHF type, participant segmentation, and the utilization of mental health services. Meanwhile, the multivariate analysis using the logistic regression test results demonstrates that age is the most influential independent variable in utilizing JKN mental health services, specifically the unproductive age group (p-value < 0.001).